The Influence of Job Pressure, Ethical Values, and Internal Control Systems on Fraud Intention: A Study on the Kaur Regency Government - Al Taufik Hidayah; Herawansyah (Jurnal Ekonomi, 2026)
This study aims to examine the influence of job pressure, ethical values, and internal control systems on fraud intention in the Kaur Regency Government. The problem of fraud in the government sector remains a significant issue because it can hinder the creation of good governance. This study uses a quantitative approach with primary data obtained through the distribution of questionnaires to 65 respondents selected using a purposive sampling technique. Data analysis was performed using multiple linear regression with the help of the SPSS version 25 program. The results show that job pressure has a positive and significant effect on fraud intention, meaning that the higher the job pressure, the higher the tendency to commit fraud. Ethical values ​​do not have a significant effect on fraud intention, so that the high or low ethical values ​​of employees have not significantly affected the tendency to commit fraud. The internal control system has a positive and significant effect on fraud intention, but the direction of the relationship obtained does not correspond to the research hypothesis, which indicates that the implementation of the internal control system in the research object has not been fully able to suppress the tendency to commit fraud. Simultaneously, the three independent variables significantly influenced fraud intention with an Adjusted R² value of 0.399, meaning that 39.9% of the variation in fraud intention can be explained by the research model, while the remaining 60.1% is influenced by other factors outside this study. The findings of this study indicate that fraud intention in government agencies is more influenced by the level of work pressure and the effectiveness of the implementation of the internal control system, while ethical values ​​have not been proven to be a factor that significantly influences the tendency to fraud. Therefore, efforts are needed to manage work pressure, strengthen the culture of integrity, and increase the effectiveness of the implementation of the internal control system to minimize the tendency to fraud in the Kaur Regency Government environment